The effect of varying kilovoltage (kVp) and tube current (mAs) on the image quality and dose of CTA head phantom / Sity Noor Ayseah Dzulkafli - Dzulkafli, Sity Noor Ayseah (2015)
In this study, the effects of kilovoltages (kVp) and tube currents (mAs) on Computed Tomography Angiography (CTA) head phantom images were investigated quantitavely using ImageJ software due to insufficient understanding on the relationship between these parameters on CT image quality and doses. The objective of this study is to investigate the effect of kilovoltages (kVp) and tube current (mAs) parameters quantitatively on several parameters namely; 1) image quality 2) dose 3) Signal to Noise Ratio (SNR) and 4) contrast. The parameters have been varied during the CT scan examination and the results have been compared for each kilovoltages (kVp) and tube currents (mAs) using ImageJ software. In brief, varying the kilovoltages (kVp) and tube current (mAs) will enhance the image quality but will also increase the dose exposure to the patient. Higher doses are one of the problems that researchers have to overcome in patient diagnosis in order to have an optimum image quality with lower doses. The results include the relationship between the parameters and image quality and also dose in selected type or arteries; Anterior Cerebral Artery (ACA), Middle Cerebral Artery (MCA) and Internal Carotid Artery (ICA) in CTA. Decreasing kVp do increase image contrasts while increasing mAs play roles in reducing the noise of the image. Finally, the suggested parameters used for brain examination is 100 kVp with 360 mAs in line with the recommended CTDIvol dose value as in Computed Tomography European Guidelines.